Mating between Echinacea angustifolia (Asteraceae) individuals increases with their flowering synchrony and spatial proximity1. Issue 1 (1st January 2014) - Ison, Jennifer L.; Wagenius, Stuart; Reitz, Diedre; Ashley, Mary V.
Abstract : Premise of the study: Although spatial distance is considered the primary factor in determining plant mating patterns, flowering time and synchrony are also likely to be important. Methods: We quantified the relationships of both distance and flowering phenology to the probability of mating between individual plants. In an experimental plot, we followed daily flowering phenology in Echinacea angustifolia, a self‐incompatible perennial pollinated by solitary bees. We assigned paternity to 832 of 927 seedlings from 37 maternal plants using 11 microsatellite loci. Potential pollen donors included the experiment plot's 202 flowering plants and a nearby plot's 19 flowering plants. For each maternal plant sampled, we examined the pollen pool by quantifying correlated paternity and the effective number of pollen donors. Key results: Significantly more pollinations occurred between neighboring and synchronous plants than expected under random mating, with distance being more important than flowering synchrony. The distance pollen moved varied over the course of the season, with late flowering plants mating with more distant plants compared to early or peak flowering plants. All maternal plants had a diverse set of mates (mean number of effective pollen donors = 23.7), and the composition of the pollen pools overlapped little between maternal plants. Conclusion: Both distance and flowering synchrony influenced pollination patterns in E. angustifolia . Our results suggest that pollen movement between incompatible mates and flowering asynchrony could be contributing to the reduced seed set observed in small E. angustifolia remnants. However, we also found that individual plants receive pollen from a diverse group of pollen donors.